Glucose metabolism continuous deteriorating in male patients with human immunodeficiency virus accepted antiretroviral therapy for 156 weeks - Liu, Da-Feng; Zhang, Xin-Yi; Zhou, Rui-Feng; Cai, Lin; Yan, Dong-Mei; Lan, Li-Juan; He, Sheng-Hua; Tang, Hong (World journal of diabetes, 2023)
The dynamic characteristics of glucose metabolism and its risk factors in patients living with human immunodeficiency virus (PLWH) who accepted primary treatment with the efavirenz (EFV) plus lamivudine (3TC) plus tenofovir (TDF) (EFV + 3TC + TDF) regimen are unclear and warrant investigation. To study the long-term dynamic characteristics of glucose metabolism and its contributing factors in male PLWH who accepted primary treatment with the EFV + 3TC + TDF regimen for 156 wk. This study was designed using a follow-up design. Sixty-one male treatment-naive PLWH, including 50 cases with normal glucose tolerance and 11 cases with prediabetes, were treated with the EFV + 3TC + TDF regimen for 156 wk. The glucose metabolism dynamic characteristics, the main risk factors and the differences among the three CD4+ count groups were analyzed. In treatment-naive male PLWH, regardless of whether glucose metabolism disorder was present at baseline, who accepted treatment with the EFV + 3TC + TDF regimen for 156 wk, a continuous increase in the fasting plasma glucose (FPG) level, the rate of impaired fasting glucose (IFG) and the glycosylated hemoglobin (HbA1c) level were found. These changes were not due to insulin resistance but rather to significantly reduced islet β cell function, according to the homeostasis model assessment of β cell function (HOMA-β). Moreover, the lower the baseline CD4+ T-cell count was, the higher the FPG level and the lower the HOMA-β value. Furthermore, the main risk factors for the FPG levels were the CD3+CD8+ cell count and viral load (VL), and the factors contributing to the HOMA-β values were the alanine aminotransferase level, VL and CD3+CD8+ cell count. These findings provide guidance to clinicians who are monitoring FPG levels closely and are concerned about IFG and decreased islet β cell function during antiretroviral therapy with the EFV + 3TC + TDF regimen for long-term application.